Flexural Stress-Strain Behavior of RC Beams Made with Partial Replacement of Coarse Aggregates with Coarse Aggregates from Old Concrete: Part-1: 1:2:4 Ratio - Oad, M.; Buller, A. H.; Memon, B. A.; Memon, N. A. (Engineering, Technology & Applied Science Research, 2018)
Occupancy, particularly in urban areas, requires more space than ever. Space constraints need erection of high rise buildings in place of short height buildings. This need demolishing of old structures which creates huge quantities of demolished concrete. One of its best disposals is its use in new concrete. Therefore, this research work uses 50% replacement of natural coarse aggregates with coarse aggregates from old concrete to study the flexural stress-strain behavior of reinforced concrete beams. Total of 12 reinforced concrete beams (900x150x150 mm) were cast with 2#4 bars in tension and 2#4 bars in compression zones. Ordinary Portland cement with hill sand and crush aggregate was used in 1:2:4 proportions. Water cement ratio used is 0.54. The beams were cast in two batches, one with 100% natural aggregates and another with 50% natural coarse aggregates replaced with coarse aggregates from old concrete. In each batch 3 beams were cured for 7 and 28 days respectively. After curing all beams were tested with central point load. The beams were monitored at regular intervals for load, displacement, strain and load until first crack. The beams under study were compared with the controlled specimen. The results were in good agreement with the normal concrete specimen. Maximum reduction in flexural stress is recorded as 8.8% for 7-day cured beams and 5.52% for 28-day cured specimen. Thus, the use of coarse aggregates from demolished concrete in new concrete is proved to be promising partial replacement of coarse aggregate in terms of flexural stress-strain relationship.